2018
DOI: 10.1177/2379298118810845
|View full text |Cite
|
Sign up to set email alerts
|

Social Change Model of Leadership Development: A 4-Year Program

Abstract: The social change model (SCM) of leadership development defines all students as potential leaders. Service acts as a powerful means for developing leadership skills within our students. After the 20th anniversary celebration by the International Leadership Association of the SCM, the authors wanted to illustrate how practice can inform research as they applied the model to a 4-year leadership program. The President’s Leadership Fellows is a 4-year program where all students have an opportunity to develop into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Studies have shown that engaging with communities, such as through service-learning, provides leaders with opportunities to reflect on their beliefs and principles as they are exposed to diverse perspectives and experiences that challenge their existing assumptions. This self-reflection not only allows leaders to gain a deeper understanding of themselves and their roles in society but also informs their approach to leadership by fostering a greater sense of responsibility and commitment to serving the common good (Buschlen & Dvorak, 2011;Dixon et al, 2019).…”
Section: Community/society Valuementioning
confidence: 99%
“…Studies have shown that engaging with communities, such as through service-learning, provides leaders with opportunities to reflect on their beliefs and principles as they are exposed to diverse perspectives and experiences that challenge their existing assumptions. This self-reflection not only allows leaders to gain a deeper understanding of themselves and their roles in society but also informs their approach to leadership by fostering a greater sense of responsibility and commitment to serving the common good (Buschlen & Dvorak, 2011;Dixon et al, 2019).…”
Section: Community/society Valuementioning
confidence: 99%
“…In this respect, each individual is seen to have the capacity to lead, depending on the level of readiness and openness of the individual. The SCM encompasses seven values which are categorised into three domains: individual values (consciousness of self, congruence, and commitment), group process values (collaboration, common purpose, and controversy with civility), and community/societal values (citizenship) (Dixon, Wales, Pennington, & Calega, 2018;HERI, 1996;Komives & Wagner, 2017). The centrality of this model is individual self-knowledge and capacity to engage others in collaborative work.…”
Section: Social Change Model Of Leadership Developmentmentioning
confidence: 99%
“…Co‐curricular student leadership programs range in size and duration. Programs can include one‐time experiences such as an hour‐long workshop for student organization leaders or a full‐day retreat for a university programming board; a workshop series or short‐term training such as a business leadership lecture series; or a sequential program such as a 4‐year, co‐curricular leadership program based on the social change model of leadership development (SCM; Dixon, Wales, Pennington, & Calega, 2019; HERI, 1996; Komives et al., 2011). If these co‐curricular programs abide by the industry's best‐practices, they should be intentionally designed with clear learning outcomes to empower students to develop their leadership skills, knowledge, and/or abilities (Gehrke, 2006).…”
mentioning
confidence: 99%